Aplikacation of Learning Start with a Question (LSQ) Strategy in Improving the Activeness of Questioning and Learning Outcomes of Islamic Religious Education - Mawarwati, Mawarwati; Kadir, St. Fatimah; Rahmawati, Rahmawati (Dirasah: Jurnal Pendidikan Islam, 2025)
Through the use of the Learning Start with a Question technique, this research seeks to improve the fifth-grade students' active question-asking behavior and learning results. Classroom Action study (CAR), which includes planning, implementing, observing, and reflecting processes, is the study methodology employed. At SD Negeri 83 Kendari, this study was carried out. For the school year 2021–2022, 29 pupils in class V served as the study's subjects. Both qualitative and quantitative data analysis methods are used. Data from observations of instructor and student activities are used in qualitative data analysis, whereas data on the results of student learning are used in quantitative data analysis. In cycle I, not all teacher and student learning activities were in line with the Learning Start with a Question learning steps, according to the findings of  observations,  whereas in  cycle  II,  the  Learning Start With a Question learning steps were appropriate and demonstrated a very good category. According to the study cycle's findings, instructor participation was inadequate at the first meeting, with a percentage of 70.6%, and rather excellent at the second meeting, with a percentage of 78.6%. Cycle II received a percentage of 86.6% in the "good" category at Meeting  1  and  a  percentage  of  92%  in  the  "very  good" category at Meeting II. With a percentage of 71.6%, the first cycle study findings based on student activity sheets fell into the "pretty good" category, and in the second meeting, a value of 78.3% was discovered. While the second cycle received a percentage of 76.6% in the first meeting with a fairly good category, and  a percentage of  83.3% with  a very excellent category  at  the  second  meeting.  In  cycle  I,  the  average response rate among students who were actively asked was 3.5%, but in cycle II, it increased to 4.21% on average. The cycle I student learning objectives were attained by 68.9% of students, while cycle II had an increase of 79.31%. The adoption of the Learning Start With a Question technique was able to improve the activeness of asking questions and student learning outcomes in class V at SD Negeri 83 Kendari, according to the findings of these observations and test results.